EFFECTS OF SYNDICATE AND GUIDED-PRACTICE TRAINING METHODS ON OCCUPATIONAL HEALTH AND SAFETY COMPETENCIES OF WORKERS IN THE CONSTRUCTION INDUSTRY IN OYO STATE, NIGERIA (2016)
Construction work and industry, although highly important to Nigeria’s developmental processes, is characterised by high level of risks occurrence and hazards. The trend is exacerbated by the insecure manner in which the construction workers are recruited, placed and managed as well as non-enforcement of existing safety laws in the sector. This raises concern about the type of safety training provided in the industry and the instructional method used in imparting such safety trainings. Previous studies have focused largely on the causes, prevention, control, safety legislations and provision of safety trainings with little emphasis on safety training instructional methods. This study, therefore, determined the effects of syndicate (STM) and guided-practice (GpTM) training methods on occupational health and safety competencies (OHSC) of workers in the construction industry in Oyo State, Nigeria. The moderating effects of employees’ literacy level and employment status were also examined. This study was anchored on multiple cause and social learning theories while the pretest-posttest, control group quasi experimental design with a 3x3x2 factorial matrix was adopted. Purposive sampling technique was employed in selecting three reputable construction organisations in Oyo State. The workers in the three organisations who met the study’s inclusion criteria were randomised into STM, (12), GpTM (11) and Lecture method (12) (Control) groups while treatment lasted six weeks. Construction Industry Occupational Health and Safety Competencies Questionnaire (r=0.85), training guides for STM, GpTM and lecture method were used for data collection. Data were analysed using descriptive statistics, Analysis of covariance and Scheffe post-hoc test at 0.05 level of significance. Participants were male (80.0%) and female (20.0%) with a mean age of 34 years; 54.3% and 45.7% were on permanent and temporary employments respectively. Their levels of literacy status were: low (37.1%), medium (34.3%) and high (28.6%). There was a significant main effect of treatment on workers’ OHSC (F (2, 17) = 22.28, partial η^2= .72). Participants exposed to STM obtained the highest posttest OHSC mean ( = 175.42) followed by those in GpTM ( = 111.00) and control ( = 82.58) groups. There were no significant main effects of literacy level and employment status on OHSC. There was a significant two-way interaction effect of treatments and literacy on OHSC (F (4, 17) = 3.18, partial η^2= .43) but the two-way interaction effects of treatment and employment status, and employment status and literacy level were not significant. Also, three-way interaction effect of treatment, literacy level and employment status on OHSC was not significant. Syndicate and guided-practice training methods were effective in enhancing the occupational health and safety competencies of construction workers regardless of their literacy level and employment status. Both training methods should, therefore, be employed regularly in safety trainings to achieve improved occupational health and safety competencies in the Nigerian construction industry.